A standardized extract of the fruit of Hovenia dulcis alleviated alcohol-induced hangover in healthy subjects with heterozygous ALDH2: A randomized, controlled, crossover trial. (14th September 2017) - Kim, Hoejin; Kim, You Jin; Jeong, Hye Yun; Kim, Ji Yeon; Choi, Eun-Kyung; Chae, Soo Wan; Kwon, Oran
Abstract: Ethnopharmacological relevance: Hovenia dulcis, known as the oriental raisin tree, is mainly found in East Asia. It has long been used as traditional folk remedies for alcohol intoxication. Aim of the study: To examine the anti-hangover effect of Hovenia dulcis Thunb. fruit extract (HDE) in a randomized controlled crossover trial. Materials and methods: Twenty-six eligible male adults with heterozygous ALDH2 (23.7±0.3 years old) consumed 360 mL of Korean Soju (50 g alcohol) together with HDE (2460 mg) or matched placebo with subsequent crossover. The blood samples were taken at baseline and 1, 4, and 12 h post-treatment. Results: Blood alcohol, acetaldehyde, and total hangover scores were highest at 1 h post-treatment with no difference between groups, but declines in hangover symptom scores were significant in the HDE group compared to the placebo group. Significant differences between groups were also observed on interleukin (IL)-6, IL-10, IL-10/IL-6 ratio, and aspartate aminotransferase levels, but not on endotoxins. Pearson correlation analysis revealed a positive correlation between total hangover symptom scores and IL-6 and IL-10 level. Further analyses by CYP2E1 polymorphism at rs10776687, rs2031920, rs3813867, and rs4838767 alleles showed a reversed association, suggesting that CYP2E1 polymorphism might be an effect modifier. Conclusions: The results suggest that a favorable effect of HDE on alcohol hangovers might be associated with enhancing homeostatic regulation of inflammatory response. The magnitude of impact might be different in the presence of CYP2E1 polymorphism. Graphical abstract: Highlights: The anti-hangover effect of HDE was tested on healthy subjects with heterozygous ALDH2. Headache, dizziness, nausea, and weakness were significantly alleviated. The favorable effect appeared to be associated with inflammation w/o endotoxemia. The magnitude of effects might be different in subjects with CYP2E1 polymorphism.